Modelling the Nonlinear Wave Motion within the Scope of the Fractional Calculus - Atangana, Abdon; Demiray, Seyma Tuluce; Bulut, Hasan (Hindawi Ltd, 2014)
The aim of this paper was to first extend the model describing the nonlinear wave movement to the concept of noninteger order derivative. The extended equation was investigated within the scope of an iterative method. The stability and convergence analysis of the iteration method for this extended equation was presented in detail. The uniqueness of the special solution was also investigated. A resume of the method for solving this equation was provided. The algorithm was used to derive the unique special solution for given initial conditions.
Keywords: Kadomtsev-Petviashvili Equation